Hubungan Faktor Lingkungan Fisik Rumah terhadap Kejadian TB Paru di Wilayah Kerja Puskesmas Panjang, Lampung - Agung Aji Perdana; Yolan Sasana Putra (Jurnal Kesehatan, 2018)
WHO in 2015 revealed that six of the countries contribute for 60% of new cases of Pulmonary TB, one of which is Indonesia. Houses that do not meet health requirements was one of the influential factors in the spread of bacteria tuberculosis. Pulmonary TB cases in Lampung Province in 2014 were 108 cases, of which 83 cases occurred at Panjang Community Health Centre. The condition of houses in the District of Panjang was only 26.28% that qualify healthy homes. This study was to identify the relationship physical environment of the house and pulmonary TB in Panjang Community Health Centre. This was a case-control study with the number of samples as many 50 cases of positive pulmonary tuberculosis patients and 50 control, not pulmonary tuberculosis patients and applied logistic regression analysis. The result showed that pulmonary TB was closely related to crowded household, ventilation, lighting, humidity of the house and lighting was the most important indicators in Panjang Community Health Centre. A healthy home and healthy life behavior were keys to reducing the risk of transmission of pulmonary tuberculosis.